2018
DOI: 10.1002/ana.25169
|View full text |Cite
|
Sign up to set email alerts
|

Activation of pial and dural macrophages and dendritic cells by cortical spreading depression

Abstract: The findings suggest that activation of pial macrophages may be more relevant to cases where aura and migraine begin simultaneously, that activation of dural macrophages may be more relevant to cases where headache begins 20 to 30 minutes after aura, and that activation of dural macrophages may be mediated by activation of migratory DCs in the subarachnoid space and dura. The anatomical relationship between TRPV1-positive meningeal nociceptors, and dural macrophages and DCs supports a role for these immune cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…It was recently used to image peripheral tissues such as immune cell infiltration in the bone after fracture, inflamed pannus tissue in osteoarthritis, the activation of macrophage and stroma in the synovial tissue of patients with rheumatoid arthritis, and in the neuroforamen of patients suffering from sciatica . Our findings in migraine demonstrate that inflammation is consistently present in a pain‐sensitive tissue, thereby reinforcing results from preclinical studies . From our results, however, we cannot conclude whether the elevated TSPO signals observed in MWA patients reflect increased protein expression, increased cellular density, or both.…”
Section: Discussionsupporting
confidence: 72%
“…It was recently used to image peripheral tissues such as immune cell infiltration in the bone after fracture, inflamed pannus tissue in osteoarthritis, the activation of macrophage and stroma in the synovial tissue of patients with rheumatoid arthritis, and in the neuroforamen of patients suffering from sciatica . Our findings in migraine demonstrate that inflammation is consistently present in a pain‐sensitive tissue, thereby reinforcing results from preclinical studies . From our results, however, we cannot conclude whether the elevated TSPO signals observed in MWA patients reflect increased protein expression, increased cellular density, or both.…”
Section: Discussionsupporting
confidence: 72%
“…12 Dural macrophages line blood vessels and connective tissues, responding to inflammatory stimuli immediately. 29 A previous study found that cortical spreading depression-induced activation of pial and dural macrophages is more likely to increase inflammation in which meningeal nociceptors function. 29 In this study, we observed that EA significantly decreased the number of immune cells.…”
Section: Discussionmentioning
confidence: 98%
“…29 A previous study found that cortical spreading depression-induced activation of pial and dural macrophages is more likely to increase inflammation in which meningeal nociceptors function. 29 In this study, we observed that EA significantly decreased the number of immune cells. Therefore, we detected a reduction in neuropeptides and inflammatory factors using ELISA.…”
Section: Discussionmentioning
confidence: 98%
“…Note that the pial arterioles and veins are not connected to the dural vessels. Though these two vascular structures are physically adjacent, they form completely unconnected vascular networks 44 , 45 .…”
Section: Introductionmentioning
confidence: 99%